High-resolution BOES Spectroscopy of Raman-scattered He iiλ6545 in Young Planetary Nebulae - Jin Lim; Seok-Jun Chang; Jaejin Shin; Hee-Won Lee; Jiyu Kim; Hak-Sub Kim; Bo-Eun Choi; Ho-Gyu Lee (The Astrophysical Journal)
Young planetary nebulae (PNe) are characterized by their hot central stars and the presence of abundant neutral and molecular components, which result from significant mass loss during the asymptotic giant branch phase of stellar evolution. Far-UV He  ii λ 1025 line photons produced near the central star can undergo Raman scattering by hydrogen atoms, creating a broad emission feature centered at ~6545 Å. We conducted high-resolution spectroscopy of 12 young PNe from 2019 April to 2020 March using the Bohyunsan Observatory Echelle Spectrograph. Building on the study by Choi and Lee, who identified Raman-scattered He  ii at 6545 Å in NGC 6881 and NGC 6886, we report new detections of this feature in NGC 6741 and NGC 6884. Profile fitting reveals that the velocity of the H  i component relative to the He  ii emission region ranges from 26 to 33 km s ^−1 in these PNe. Using photoionization modeling, we estimate the line flux of He  ii λ 1025 and derive Raman conversion efficiencies of 0.39, 0.21, 0.24, and 0.07 for NGC 6881, NGC 6741, NGC 6886, and NGC 6884, respectively. These results, combined with radiative transfer modeling, suggest the presence of H  i components with masses around 10 ^−2 M _⊙ , moving outward from the central He  ii emission region at speeds characteristic of the slow stellar wind from a mass-losing giant star.